2022
DOI: 10.1155/2022/4510900
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance Evaluation of FilmArray BioFire RP2.1 and MAScIR 2.0 Assays for SARS-CoV-2 Detection

Abstract: Background. RT-PCR is the gold standard for COVID-19 diagnosis, but the lack of standardization of assays, whose diagnostic performance may widely vary, complicates the interpretation of the discrepancies that may be encountered. Study design. We conducted a retrospective study over a ten-month period at the Central Laboratory of Virology of Ibn Sina University Hospital of Rabat. We included nasopharyngeal swabs, positive and negative for SARS-CoV-2 on FilmArray BioFire® Respiratory Panel 2.1 Plus, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…To date, a single retrospective study, recently published and carried out in our laboratory, evaluated the FilmArray BioFire RP2.1 (Respiratory 2.1 Panel) kit using our MAScIR SARS-CoV-2 M 2.0 kit as a reference kit [ 18 ]. In this study, there were no discordant results between MAScIR and FilmArray BioFire RP2.1 with regards to negative samples.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a single retrospective study, recently published and carried out in our laboratory, evaluated the FilmArray BioFire RP2.1 (Respiratory 2.1 Panel) kit using our MAScIR SARS-CoV-2 M 2.0 kit as a reference kit [ 18 ]. In this study, there were no discordant results between MAScIR and FilmArray BioFire RP2.1 with regards to negative samples.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lade H et al indicated that the FilmArray TM RP assay is easy to work and provide rapid identification of respiratory viruses [ 57 ]. Moreover, Tazi S et al [ 31 ] showed that the estimated sensitivity and specificity of FilmArray, compared with the MAScIR SARS-CoV-2 M kit 2.0, were 100% and 79.2%, respectively. Recently, Livingstone et al [ 58 ] showed that the application of FilmArray TM RP 2.1 assay for COVID-19 remarkably reduced the time to obtain results spent on assessment cohort wards and the proportion of hospital-acquired COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative result for each target was automatically interpreted by the software according to the endpoint melting curve data. A pathogen was recorded as detected if at least one of its corresponding assays was positive [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, Tazi et al compared two PCR assays, BioFire RP2.1 plus and their laboratory's reference test, MAScIR SARS-CoV-2 M kit 2.0, a triplex real-time RT-PCR, using TaqMan technology, targeting SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) and S genes. 5 The results were compared, and each discrepant sample with sufficient volume underwent a third test using ARGENE® SARS-CoV-2 R-GENE kit, a triplex real-time RT-PCR, which also used TaqMan technology, targeting SARS-CoV-2 N (Nucleocapsid) and RdRp genes. Of the 80 specimens positive for BioFire RP2.1 Plus, 21 (26.3%) had discordant results on MAScIR, and only 11 could be tested on ARGENE, revealing negative results in five cases.…”
mentioning
confidence: 99%
“… 4 These results led to them consequently retaining the SARS-CoV-2 positive results of these discordant samples on BioFire RP2.1 plus, regardless of the detection of one or both targets. 5 …”
mentioning
confidence: 99%